Multiple intracerebral hemorrhages associated with lipohyalinosis: a case report. (June 2020) - Torimitsu, Suguru; Abe, Hiroyuki; Ikemura, Masako; Gonoi, Wataru; Ishida, Masanori; Makino, Yohsuke; Iwase, Hirotaro
Highlights: We report a fatal case of multiple cerebral hemorrhages. The decedent was considered to be in a state of lipohyalinosis. It is important to conduct brain tissue examinations to make a correct diagnosis. Abstract: In this paper, we report a fatal case of multiple intracerebral hemorrhages associated with lipohyalinosis. A woman in her sixties was admitted to the hospital, where she was subsequently diagnosed with intracerebral hemorrhage. While hospitalized, she suffered several intracerebral hemorrhages and died 67 days after admission. During her hospital stay, she was also diagnosed with cerebral amyloid angiopathy (CAA). The results of autopsy and postmortem computed tomography indicated that the cause of death was a fourth hemorrhage from the cortex to the subcortex in the left parietal lobe. Microscopy further revealed eosinophilic and structureless material in the vessel walls of the brain surface. In addition, these blood vessel walls did not stain by Congo Red stain or immunohistochemical staining using the anti-amyloid β-protein antibody, but they were stained blue with the azocarmine stain. Thus, the decedent was considered to be in a state of lipohyalinosis. To the best of our knowledge, this is the first case report of a death after multiple intracerebral hemorrhages as a result of lipohyalinosis. Based on these findings, the possibility cannot be excluded that there may be a case that has been clinically diagnosed as CAA despite the true cause of multiple intracerebral hemorrhages being small vessel disease such as lipohyalinosis. Therefore, it is important to conduct brain tissue examinations to make a correct diagnosis. Graphical abstract: Image, graphical abstract